Antiemesis effect and brain fMRI response of gastric electrical stimulation with different parameters in dogs. Issue 7 (July 2014) - Yu, X.; Tu, L.; Lei, P.; Song, J.; Xu, H.; Hou, X.
Abstract Background The aims of this study were to investigate the effect of gastric electrical stimulation (GES) with different parameters on emesis induced by apomorphine, and possible center mechanisms by brain functional magnetic resonance imaging (fMRI). Methods Six dogs implanted with electrodes on gastric serosa were used in this study. Part 1: Apomorphine was injected in the control session and GES sessions. GESs with different parameters were applied in GES session. Gastric slow waves and emesis and behaviors suggestive of nausea were recorded in each session. Part 2: Each dog was anesthetized and given GESs with different parameters or sham stimulation for 15 min after baseline (5 min), respectively. The location of cerebral activation induced by GES was investigated by fMRI. Key Results Apomorphine induced emesis and behaviors suggestive of nausea, and gastric dysrhythmia. The emesis frequency in control session was 5.5 ± 0.99, and symptoms score was 22.17 ± 1.01. GES with short pulse and long pulse could not improve emesis and symptoms induced by apomorphine. The emesis frequency (4.5 ± 0.76 in short pulse and 6.33 ± 1.05 in long pulse) and symptoms scores had no significant difference compared to control session (each p > 0.05). GES with trains of short pulse reduced emesis time frequency (3.83 ± 0.7, p = 0.042 vs control) and symptoms score (p = 0.037 vs control) obviously. Brain fMRI showed that GES with short pulse and long pulse activated brain stem region, and trains of short pulse made amygdala and occipital lobe activation. Conclusions & Inferences Apomorphine induced emesis and gastric dysrhythmia. GES with trains of short pulses relieves emetic responses through activation of amygdala region.